Post-harvest loss along the watermelon value chain in the tropics (2021)
The growing realization of nutritional and health benefits, and the potential of watermelon (Citrullus lanatus L.) as a cash producing crop has renewed interest in reducing loss in its postharvest handling. Information on the extent of loss in different parts of its post-harvest system under tropical conditions is scarce. Key constraints identified by producers were insect infestation, insufficient working capital, poor handling of produce, lack of access to market, and lack of technology while inadequate access to funds, lack of storage facilities, and poor packaging of produce were identified by marketers. Post-harvest trouble spots were determined through adequate evaluation of the proportion of loss and associated factors along the watermelon supply chain. The majority of producers and marketers experienced loss of up to 40%, some >60%. Interventions in trouble-spots can have an impact on the reduction of postharvest loss. A better understanding of loss along the supply chain was developed which can lead to the determination of effective strategies to manage watermelon loss in the tropics.